Dampak Pasca Penambangan Emas Bagi Kerusakan Lahan di Sekitar Aliran Batang Palangki di Kenagarian Muaro Kecamatan Sijunjung Kabupaten Sijunjung - Junita, Lia; Edial, Helfia; Juita, S.Pd., M.Si, Erna (Pendidikan Geografi, 2014)
ABSTRACTÂ This research aims to describe and analyze The Impact of Pasca Gold Mining for Damage of Land in Flow Around Batang Palangki in the Kenagarian Muaro Kecamatan Sijunjung Kabupaten Sijunjung, as seen from the extensive damage to land, land use changes, changes in the direction of flow of the river. This research is descriptive quantitative. The object of research is the area around the flow Batang Palangki be found in the Kenagarian Muaro Kecamatan Sijunjung Kabupaten Sijunjung. The sample in this research was taken by purposive sampling technique, the research sample consisted of three sample areas. Materials and tools used in this research is in the form of GPS, maps and gauges. Data analysis methods used in this research to calculate the area damage of land is by using the grid method. Results of the research include: (1) The land area is changing, 2.25 ha in sample I. 4.5 ha in sample II and III. (2) many ex-mining land into wasteland after being abandoned. (3) The effect of mining, cause the direction of the river flow moving and wide.